2022
DOI: 10.1002/smll.202204350
|View full text |Cite
|
Sign up to set email alerts
|

High‐Yield, Magnetic Harvesting of Extracellular Outer‐Membrane Vesicles fromEscherichia coli

Abstract: Extracellular outer‐membrane vesicles (OMVs) are attractive for use as drug nanocarriers, because of their high biocompatibility and ability to enter cells. However, widespread use is hampered by low yields. Here, a high‐yield method for magnetic harvesting of OMVs from Escherichia coli is described. To this end, E. coli are grown in the presence of magnetic iron‐oxide nanoparticles (MNPs). Uptake of MNPs by E. coli is low and does not increase secretion of OMVs. Uptake of MNPs can be enhanced through PEGylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…We hypothesized that the enrichment of target proteins in the lumen of OMVs would be an 20 To test this, we first established a secretion system to translocate the overexpressed protein into the periplasm, facilitating its subsequent envelopment into the OMVs. A model protein Spy in our lab fusing with the pelB signal peptide at the N-terminus was cloned into the pET-21a vector (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that the enrichment of target proteins in the lumen of OMVs would be an 20 To test this, we first established a secretion system to translocate the overexpressed protein into the periplasm, facilitating its subsequent envelopment into the OMVs. A model protein Spy in our lab fusing with the pelB signal peptide at the N-terminus was cloned into the pET-21a vector (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the enrichment of target proteins in the lumen of OMVs would be an attractive way for intracellular protein delivery in at least two aspects: the low cost of producing the OMVs by culturing E. coli and directly labeling target protein in OMVs with various dyes. 20 To test this, we first established a secretion system to translocate the overexpressed protein into the periplasm, facilitating its subsequent envelopment into the OMVs. A model protein Spy in our lab fusing with the pelB signal peptide at the N-terminus was cloned into the pET-21a vector (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…OMVs are naturally evolved vehicles for intraspecies and interspecies biomolecule transportation of nucleic acid and proteins. We hypothesized that the enrichment of target proteins in the lumen of OMVs would be an attractive way for intracellular protein delivery in at least two aspects: the low cost of producing the OMVs by culturing E. coli and directly labeling the target protein in OMVs with various dyes . To test this, we first established a secretion system to translocate the overexpressed protein into the periplasm, facilitating its subsequent envelopment into the OMVs.…”
Section: Resultsmentioning
confidence: 99%
“…23−25 We hypothesized that the enrichment of target proteins in the lumen of OMVs would be an attractive way for intracellular protein delivery in at least two aspects: the low cost of producing the OMVs by culturing E. coli and directly labeling the target protein in OMVs with various dyes. 26 To test this, we first established a secretion system to translocate the overexpressed protein into the periplasm, facilitating its subsequent envelopment into the OMVs. A model protein, Spy, which functions as a periplasmic chaperone protein in E. coli, was cloned into the pET-21a vector after fusion with a pelB signal peptide at the N-terminus (Figure 2a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…They are attributed to nutrient or information exchanges between bacterial cell-to-cell communications. [24][25][26] Many studies suggested that parent cells tend to re-acquire large quantities of substances coated by their own membrane vesicles by internalization or membrane fusion, which enables selectively targeted delivery. 27,28 In comparison to traditional liposomal formulations, bacterial membrane vesicles are relatively easier to harvest in large quantities and display functional biomolecules by bacterial engineering, thus promising wide applications in biomedicine.…”
Section: Introductionmentioning
confidence: 99%